The barber of Seville - Sterbini, Cesare, 1784-1831 (Opera classics library., 2005)
A comprehensive guide to Rossini's THE BARBER OF SEVILLE, featuring insightful and in depth Commentary and Analysis, a complete, newly translated Libretto with Italian/English side-by side, and over 35 music highlight examples.